Burnout and Metabolic Syndrome in Female Nurses: An Observational Study - Chico Barba, Laura Gabriela; Jiménez-Limas, Karime; Sánchez-Jiménez, Bernarda; Sámano, Reyna; Hernández Rodríguez, Ana Lilia; Castillo-Pérez, Rafael; Tolentino, Maricruz (My University, 2019)
Nurses are at risk of having burnout due to workload and job stress—studies have reported that chronic stress is associated with metabolic syndrome. This study aimed to assess the association between burnout and metabolic syndrome in a sample of female nurses. Data were collected from a cross-sectional study from 2016 to 2018 in a tertiary hospital in Mexico City. All nurses that work in the hospital were invited to participate. Information pertaining to sociodemographic (age, education level), work (labor seniority, service area, shift work), anthropometric (weight, waist circumference, blood pressure) and biochemical (glucose, serum lipids) variables were collected. Burnout was assessed using the Maslach Burnout Inventory test, and metabolic syndrome was defined according to the International Diabetes Federation criteria. A total of 168 nurses participated with a median age of 44 years. The prevalence of burnout and metabolic syndrome was 19.6% and 38.7%, respectively. There was no association between burnout and metabolic syndrome (p = 0.373). However, associations of emotional exhaustion (aOR: 14.95; 95% CI: 1.5–148.7), personal accomplishment (aOR: 0.13; 95% CI: 0.01–0.99), and night shift (aOR: 12.39; 95% CI: 1.02–150.5) with increased waist circumference were found. Strategies are needed to prevent burnout and metabolic syndrome in nurses, especially in those who work at night shift.